Acceptability of the live biotherapeutic LACTIN-V (Lactobacillus crispatus CTV-05) among young women at high risk of HIV acquisition in South Africa: data from the phase 2 placebo-controlled trial - Hemmerling, A.; Govender, V.; Dong, K.; Dong, M.; Pillay, Sooseela; Ndung’u, T.; Bhoola, A.; Moodley, J.; Casillas, G.; Lagenaur, L.; Mitchell, C. M.; Kwon, D. S.; et al. (Frontiers in Reproductive Health, 2025)
IntroductionLive biotherapeutic products (LBPs) containing Lactobacillus crispatus may optimize the vaginal microbiota, reduce genital inflammation, and protect against HIV acquisition. Determining acceptability of LBPs among African women at high risk of HIV is essential to guide product development.MethodsThe phase 2 double-blind randomized placebo-controlled trial recruited young sexually active cis-women with vaginal dysbiosis from a community-based research clinic. Following antibiotics (oral metronidazole), participants were randomized (2:1) to receive 11 doses of LACTIN-V (2 × 109 L. crispatus CTV-05) or placebo over 4 weeks. A questionnaire assessed product acceptability.ResultsForty-five young Black South African women were randomized to LACTIN-V (N = 32) or placebo (N = 13). Forty-two (93.3%) had an active sexual partner. Adherence was high with 36 participants (80.0%) completing all 11 doses. Of the 43 participants who completed the acceptability questionnaire, 38 (88.4%) were satisfied using the vaginal applicator and 41 (95.5%) confirmed ease of use. For 14 (32.5%) participants, product use without the partner knowing was important. Thirty-one (72.1%) participants felt that partner approval for product use was not important. On Likert scales of 0–10 (lowest to highest), agreement with positive product attributes (effective, comfortable, easy to use) scored at means of ≥6.7. Negative product attributes (dosing, leakage, vaginal dryness, partner's disapproval) were rated less important with lower mean scores ≤3.2. Overall, 75% of participants would use the product again, with no significant difference between study arms.ConclusionsYoung South African women at high risk of HIV found the LACTIN-V study product highly acceptable and easy to use.Clinical Trial Registration[clinicaltrials.gov], identifier [NCT05022212].